Carbon Flow in Mercury Biomethylation by Desulfovibrio desulfuricans - Berman, Mitchell (1990)
Radiocarbon incorporation from pyruvate and serine into monomethylmercury by Desulfovibrio desulfuricans was consistent with the proposal that the methyl group originates from C-3 of serine. Immunodiagnostic assays measured 4 to 35 μg of tetrahydrofolate and 58 to 161 ng of cobalamin or a closely related cobalt porphyrin per g of cell protein in D. desulfuricans. The light-reversible inhibition of mercury methylation by propyl iodide in D. desulfuricans indicates methyl transfer by a cobalt porphyrin.